2000
DOI: 10.1136/emj.17.5.337
|View full text |Cite
|
Sign up to set email alerts
|

Next day telephone follow up of the elderly: a needs assessment and critical incident monitoring tool for the accident and emergency department

Abstract: Background-Patients over the age of 75 years comprise an increasing proportion of accident and emergency (A&E) department attendances. Within this group there is a high incidence of comorbidity, which mandates eVective discharge coordination from the A&E department. Objectives-The aims of this study were to assess the needs of these patients the day after discharge, target patients for appropriate interventions and identify critical incidents. Setting-The study was undertaken in a district general hospital A&E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 10 publications
1
49
1
Order By: Relevance
“…Similar results were also found by Bean and Waldron (1995), Bowman, Howden, Allen, Webster, and Thompson (1994) and Poncia, Ryan, and Carver (2000). Bean and Waldron (1995) discovered that when a postdischarge phone call was placed 48 hours after discharge, many patients had retained very little of the discharge information taught to them prior to leaving the hospital.…”
Section: Postdischarge Outcomessupporting
confidence: 84%
“…Similar results were also found by Bean and Waldron (1995), Bowman, Howden, Allen, Webster, and Thompson (1994) and Poncia, Ryan, and Carver (2000). Bean and Waldron (1995) discovered that when a postdischarge phone call was placed 48 hours after discharge, many patients had retained very little of the discharge information taught to them prior to leaving the hospital.…”
Section: Postdischarge Outcomessupporting
confidence: 84%
“…For example, second-level CGA (performed in the ED [82,83] or, within 24 hours, at the patient's home [89]), individualised discharge plan or case management by specialised nurses or a multidisciplinary team [83,89,90], appropriate referral for primary care and community services [82,83,91], and follow-up [82,83] with ambulatory or home visit or telephone contact [92,93] have been used. Unfortunately, the paucity of randomised controlled clinical trials, together with the great variability in the type of intervention, study design (e.g., patient selection, duration of interventions and follow-up, considered outcomes) and compliance to recommended programs, can probably account for the lack of consistent results.…”
Section: Dischargementioning
confidence: 99%
“…28 Identifying the need for services One factor that may affect rates of emergency re-attendance or readmission is the capacity of ED staff to identify the need for a range of further services in patients who are not admitted or discharged. For example, when Poncia et al 29 reported a study in which 551 patients over 75 or their carers were contacted by telephone the day after discharge from an A&E department substantial unmet needs were discovered. Existing home support was felt to be insufficient in 44 (8%) cases and in need of immediate intervention in a further 45 (8%) cases.…”
Section: Satisfactionmentioning
confidence: 99%
“…As has just been indicated above [29][30][31][32][33][34] a range of circumstances that lead people to ED attendance are as much social as medical in nature and origin: self harm, violence (including domestic violence and child abuse), substance misuse, the lack of adequate social care. In addition, it is known that material deprivation is associated with raised rates of ED attendance and emergency hospital admission.…”
Section: Access To Social Care Servicesmentioning
confidence: 99%